Novel approach for the development of ultra-light, fully-thermoplastic composites. (5th March 2016) - Leal, A. Andres; Veeramachaneni, Joshi C.; Reifler, Felix A.; Amberg, Martin; Stapf, Dominik; Barandun, Gion A.; Hegemann, Dirk; Hufenus, Rudolf
Abstract: A novel approach for the development of ultra-light, fully-thermoplastic fiber reinforced composites is presented. The composite material consists of a polyolefin plastomer (POP) matrix reinforced with ultra-high molecular weight polyethylene (UHMWPE) fibers. The interfacial affinity of both polyolefins is enhanced by the deposition of a nanometer-scale polar functional plasma polymer film on the surface of the filaments within a reel-to-reel continuous process. The activated UHMWPE yarn is subsequently coated with a layer of the matrix material using a modified wire coating process in order to produce a hybrid yarn. The improved adhesion between the two materials is demonstrated by means of a specially developed yarn pull-out method that measures the UHMWPE–POP interfacial shear strength. The combination of the two techniques employed in the development of the hybrid yarn largely maintains tensile strength as well as the crystalline structure of the UHMWPE yarn as determined by wide angle X-ray diffraction. Alternate layers of woven hybrid yarn and woven pure UHMWPE yarn are then stacked and the lay-up is consolidated by hot compaction, resulting in a composite laminate with a fiber volume fraction of 0.54 and a density of 0.93 g/cm 3 . Graphical abstract: Highlights: The surface of an ultra-high molecular weight polyethylene yarn is activated at a winding speed of 44 m/min. The surface activation consists of the deposition of a nanometer-scale polar functional plasma polymer film. A modified wire coating process allows applying a thermoplastic sheath on the activated yarn at a speed of 40 m/min. The hybrid yarn thus obtained lends itself as base material for the development of ultra-light composites. The fully-thermoplastic material shows superior tensile properties with respect to other types of fiber-reinforced composites.